VALIDITY AND TECHNOLOGY INTEGRATION IN LANGUAGE ASSESSMENT - Hilola Maksudova; Dadabayeva Luiza (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Language assessment plays a crucial role in educational contexts, professional certification, and immigration processes worldwide. Despite significant advancements in testing methodologies, numerous challenges persist in ensuring valid, reliable, and fair assessment of language proficiency. This article examines key challenges in contemporary language assessment, including construct validity issues, cultural and linguistic bias, the integration of technology, and the assessment of pragmatic competence. The paper concludes with recommendations for future research and practice in language assessment, emphasizing the need for more inclusive, authentic, and comprehensive approaches that reflect the complex nature of language use in real-world contexts.